CONSTRUCTION AND USE OF DICHOTOMOUS KEYS FOR THE IDENTIFICATION OF DIFFERENT TAXONS OF VERTEBRATES IN CUBA - Armiñana-García, Rafael (2020)
Dichotomous keys are resources or tools that researchers, teachers or other personnel linked to the study of biological sciences use for the determination of diff erent species of organisms, by comparing two exclusive characters. The investigation proposes diff erent dichotomous keys, illustrated in electronic format, for the identifi cation of diff erent aquatic and terrestrial vertebrate taxa present in Cuban fauna that includes orders, families, genera and species, and that are in correspondence with the Zoology Program’s General II (Zoology of the chordates), which is taught in the Degree in Biology Education at the Central University “Marta Abreu” of Las Villas, in the Republic of Cuba. Various theoretical and empirical methods were used in the investigation in their dialectical interrelation which allowed identifying the existing defi ciencies and proposing the solution. Th e information for the diagnosis was obtained from the application of diff erent instruments, such as document review, participant observation, pedagogical test, case study, student survey and expert evaluation. In order to mitigate the diffi culties detected, and with a view to introducing for the fi rst time the illustrated dichotomous keys for vertebrates in electronic format in the Bachelor’s degree in Biology Education, they were developed and subjected to expert criteria that assessed them as relevant.